Factors associated with quality of life in active childhood epilepsy: A population-based study. (May 2015) - Reilly, Colin; Atkinson, Patricia; Das, Krishna B.; Chin, Richard F.M.; Aylett, Sarah E.; Burch, Victoria; Gillberg, Christopher; Scott, Rod C.; Neville, Brian G.R.
Abstract Background Improving health-related quality of life (HRQOL), rather than just reducing seizures, should be the principal goal in comprehensive management of childhood epilepsy. There is a lack of population-based data on predictors of HRQOL in childhood epilepsy. Methods The Children with Epilepsy in Sussex Schools (CHESS) study is a prospective, population-based study involving school-aged children (5–15 years) with active epilepsy (on one or more AED and/or had a seizure in the last year) in a defined geographical area in the UK. Eighty-five of 115 (74% of eligible population) children underwent comprehensive psychological assessment including measures of cognition, behaviour, and motor functioning. Parents of the children completed the Quality of Life in Childhood Epilepsy (QOLCE).Clinical data on eligible children was extracted using a standardised pro forma. Linear regression analysis was undertaken to identify factors significantly associated with total Quality of Life in this population. Results Factors independently significantly associated (p < .05) with total QOLCE scores were seizures before 24 months, cognitive impairment (IQ < 85), anxiety, and parent reported school attendance difficulty. These factors were also significantly associated with total QOLCE when children with IQ < 50 were excluded from analysis. Conclusions The majority of factors associated with parent reported HRQOL in active childhood epilepsy are related to neurobehavioural and/or psychosocial aspects of the condition.